Public School Superhero - Patterson, James, 1947-; Tebbetts, Christopher; Thomas, Cory (New York : Little, Brown and Company, 2015)
"In Kenny Wright's active imagination he's a world famous superhero, but in the real world he's a sixth grade "Grandma's Boy" whose struggles to fit in at his Washington D.C. inner city school will put his grades and family loyalty to the test"--Provided by publisher.
"Includes sections of comic-style illustrations"--Title page verso.
Accelerated Reader
edited hb 2015-06-16
Keywords: Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Superheroes -- Juvenile fiction; Grandmothers -- Juvenile fiction; African Americans -- Juvenile fiction; Middle schools -- Fiction; Schools -- Fiction; Superheroes -- Fiction; Grandmothers -- Fiction; African Americans -- Fiction; Humorous stories; Washington (D.C.) -- Juvenile fiction; Washington (D.C.) -- Fiction; Humorous stories